Optimization of Biological Nitrogen Fixation by Rhizobium Bacteria to Enhance Growth and Yield of Soybean (Glycine max L.) - Johannes Pardede; Noverina Chaniago; Murni Sari Rahayu (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Rhizobium bacteria play a pivotal role in soybean (Glycine max L.) cultivation through their ability to perform biological nitrogen fixation. The effectiveness of Rhizobium in increasing crop yield is influenced by the soybean variety and the inoculation dose applied. Therefore, the application of Rhizobium inoculants appropriate to soybean varieties has the potential to increase the efficiency of nitrogen utilization in a sustainable and environmentally friendly manner. This study aims to determine the effectiveness of Rhizobium strain doses on the growth and production of two soybean varieties. The study was conducted using a factorial Randomized Block Design (RBD), consisting of two factors: soybean varieties (Anjasmoro and Dega 1) and Rhizobium doses (control/without Rhizobium, 10 g/kg seed, and 15 g/kg seed). Data were analyzed using analysis of variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT) at a significance level of 5%. The results showed that the interaction between soybean varieties and Rhizobium doses had a significant effect on leaf area. The best treatment combination was obtained with the Dega 1 variety and a Rhizobium dose of 15 g/kg of seeds. The Dega 1 variety had a significant effect on seed weight per plant and per plot. This variety demonstrates superior physiological capabilities and adaptability in utilizing growing resources for seed biomass accumulation, thereby contributing to increased national soybean yields. A Rhizobium dose of 15 g/kg seed had a significant effect on the number of root nodules and the number of soybean pods. Therefore, this dosage is recommended as the standard in soybean cultivation using inoculation technology.